The Wizard of Oz [videorecording (DVD)] - Fleming, Victor, 1889-1949; Garland, Judy; Morgan, Frank, 1890-1949; Bolger, Ray; Lahr, Bert, 1895-1967; Haley, Jack, 1897-1979; Grapewin, Charles, 1869-1956; Baum, L. Frank (Lyman Frank), 1856-1919 (Warner Home Video, 2009)
Dorothy Gale lives with her Aunt Em and Uncle Henry. She has a pet dog named Toto. When Miss Gulch takes Toto away, Toto escapes and runs back to Dorothy. Soon, she runs away from home, and runs into the fake psychic, Professor Marvel. He tells Dorothy that her Auntie Em is sick, so Dorothy and Toto run back home, but a tornado comes and takes Dorothy and Toto to Oz, a place somewhere over the rainbow. She lands in Munchkinland. Her house accidentally lands on the Wicked Witch of the West's sister and Dorothy magically inherits the pair of ruby slippers that were on her feet. Glinda, the Good Witch of the North tells Dorothy to follow the Yellow Brick Road to see the Wizard so she can get back home. Along the way, she befriends Scarecrow, Tinman, and Lion. They are also seeking help from the Wizard because the Scarecrow needs a brain, Tinman needs a heart, and Lion needs courage.